Modern labor migration from Kalmykia and Tuva: economic, socio-cultural and gender aspects - Badmaeva, Nogan V.; Natsak, Organa D. (The New Research of Tuva, 2021)
The article presents a comparative analysis of contemporary migration processes in two Russian regions, geographically distant from each other, but having common historical and socio-cultural roots - the Republic of Kalmykia and the Republic of Tuva. They also have similar social and economic performance indicators, and a high level of poverty, all of which tends to push the populations out of both regions. At the same time, the background for labor migration is quite different: while Kalmykia is experiencing depopulation, Tuva’s population is growing. The authors have analyzed different stages of the migration process in Kalmykia and Tuva, ranging from making a decision to move out of the region, choosing a destination and job search channels, to "adaptability" to the peculiarities of climatic, living and socio-cultural conditions, satisfaction with the level of wages in the new region of residence, as well as further life strategies, such as timing the move or prospects of returning. Special attention was paid to the issues of preserving ethnic and religious identity in a different ethnic environment, to the surviving ties with home area, as well as to the gender aspects of labor migration.For its sources, the study relies on statistics, and on the in-depth interviews 43 respondents gave in 2021. All of them moved out of their own regions. The respondents from Tuva found the main reason for their migration in the need to pay off credit arrears and to provide for children. For respondents from Kalmykia, migration to the Far North is an opportunity to realize their professional potential and career development, since it is unattainable in their home republic. In-depth interviews confirm that labor migrants maintain close ties with their home area, express a desire to preserve their ethnic and religious identity, and tend to join or start ethnic communities in places of migration.To conclude, labor migration, despite its recurrent nature, is becoming a prolonged process, and ay in the future become a source of demographic and personnel problems for donor regions, such as Kalmykia and Tuva.
Keywords: migration processes; Republic of Kalmykia; Republic of Tuva; internal migration; labor migration; migration intentions; socio-cultural adaptation; labor migrants; gender aspect